THE INFLUENCE OF AMERICAN POPULAR CALTURE ON THE LIFESTYLE OF INDONESIA TEENAGERS - Yuki, Librilianti Kurnia; Munawaroh, Dina Al (Jurnal JOEPALLT (Journal of English Pedagogy, Linguistics, Literature, and Teaching), 2025)
American culture is growing rapidly and widely, and is easily accepted by the public. American culture and lifestyle has become a popular culture, and its development spread to various countries, including Indonesia. The influx of American culture into Indonesia in recent years has also had an impact on Indonesian teenagers, causing them to follow American lifestyle changes. The purpose of this study is to find out whether the influence of American culture on Indonesian teenagers has a positive impact on their lives or a negative impact. This research method adopts quantitative method in filling out questionnaires. The participants in this study were students of Universitas Putra Indonesia (UNPI), an age group where teenagers are easily influenced by foreign cultures that enter Indonesia.